2017
DOI: 10.1038/s41467-017-01823-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene balls for lithium rechargeable batteries with fast charging and high volumetric energy densities

Abstract: Improving one property without sacrificing others is challenging for lithium-ion batteries due to the trade-off nature among key parameters. Here we report a chemical vapor deposition process to grow a graphene–silica assembly, called a graphene ball. Its hierarchical three-dimensional structure with the silicon oxide nanoparticle center allows even 1 wt% graphene ball to be uniformly coated onto a nickel-rich layered cathode via scalable Nobilta milling. The graphene-ball coating improves cycle life and fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(74 citation statements)
references
References 41 publications
0
73
0
1
Order By: Relevance
“…Similarly, Winter's group (32) found that the cycle life of a graphite/NMC532 cell with a 77-μm-thick anode increased from 400 cycles at 20°C to 1,100 cycles in 45°C at 70% capacity retention. Most recently, researchers from Samsung (20) developed an HE cell with 5-C charging capability at 60°C. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Winter's group (32) found that the cycle life of a graphite/NMC532 cell with a 77-μm-thick anode increased from 400 cycles at 20°C to 1,100 cycles in 45°C at 70% capacity retention. Most recently, researchers from Samsung (20) developed an HE cell with 5-C charging capability at 60°C. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3), which explains the long recharge time of today's EVs at low temperatures. To enhance fast charging ability, research in the literature has been focusing on improving anode materials such as coating graphite with an amorphous silicon nanolayer (16,17) and developing new materials like lithium titanate (18,19) and graphene balls (20), and on developing new electrolytes (21,22) and additives (23). LiBs, however, are well known for their trade-off nature among key parameters (24).…”
mentioning
confidence: 99%
“…However, as lithium-ion batteries suffer from the barriers of charging rates, lifespan, and reliability, they need to be improved further [40,45,[49][50][51][52][53]. The latest research shows that adding graphene to the cathode materials of lithium-ion batteries can improve their performance [54,55]. On account of widespread prospects for new-generation EV applications, lithium-ion battery technology has attracted significant attention of numerous researchers.…”
Section: Lithium-ion Batteriesmentioning
confidence: 99%
“…4 Different 3DGNs have been prepared in the form of graphene foams, 5 graphene sponges, 6 graphene aerogels, 7 graphene mesh, 8 and graphene balls. 9 3-D graphene materials possess excellent properties including large surface areas and pore volumes, low densities, good electrical conductivities, and mechanical properties. 3DGNs have been extensively used in the fields of energy storage and conversion, including fuel cells, batteries, solar cells, and supercapacitors.…”
Section: Introductionmentioning
confidence: 99%